Elaine Steinbeck in stateroom aboard the S.S.Hav sailing from New York to Casablanca. - Unknown:::Creator:::::::::::: (2022)
Elaine Steinbeck in stateroom visits with an unidentified woman aboard the S.S.Hav sailing from New York to Casablanca. Original in safe